Рівні з позитивною парністю ізотопів 21,23Na в моделі ядерних оболонок - Hasan, A. K.; Obeed, F. H.; Rahim, A. N. (Publishing house "Academperiodika", 2020)
The energy levels and transition probabilities B(E2; ↓) i B(M1; ↓) have been investigated for 21,23Na isotopes by using the (USDA and USDB) interactions in the (sd-shell) model space. In the calculations of the shell model, it has been assumed that all possible many-nucleon configurations are specified by the (0d5/2, 1s1/2 i 0d3/2) states above 16O doubly magic nucleus. The available empirical data are in a good agreement with predictions of theoretical energy levels. Spins and parities are affirmed for new levels, transition probabilities B(E2; ↓) and B(M1; ↓) are predicted as well.